Exploitation of Tenebrio molitor larvae as biological factories for human probiotics, an exploratory study. (July 2021) - Milanović, Vesna; Cardinali, Federica; Belleggia, Luca; Garofalo, Cristiana; Pasquini, Marina; Tavoletti, Stefano; Riolo, Paola; Ruschioni, Sara; Isidoro, Nunzio; Osimani, Andrea; Aquilanti, Lucia
Graphical abstract: Highlights: Bacillus clausii dynamics in a rearing chain of mealworm larvae were studied. The results showed that B. clausii was able to grow in the insect gut. The washing of larvae affected the load of B. clausii depending on the inoculum level. Mealworms were effective biological factories for growth of probiotic B. clausii. Abstract: The exploitation of yellow mealworm ( Tenebrio molitor ) larvae for the bioaugmentation of probiotic Bacillus clausii strains was evaluated during a 7-day rearing period. qPCR was applied to evaluate the persistence and growth of B. clausii in the rearing substrate and larvae (washed and non-washed). Moreover, the effect of freeze-drying of larvae on B. clausii viability was evaluated. The results demonstrated the suitability of yellow mealworm as biological factories for the multiplication of B. clausii through a simple and inexpensive procedure, in view of the further application of larvae as foods and food ingredients. In more detail, an increase in the load of B. clausii was observed during the 7-day rearing of larvae fed wheat middlings spiked with 1 Log cells g −1 . Further research is needed to evaluate the most suitable technologies and processing parameters for obtaining yellow mealworm-based ingredients with a stable and active population of probiotic B. clausii .